Effective microwave-assisted approach to 1,2,3-triazolobenzodiazepinones via tandem Ugi reaction/catalyst-free intramolecular azide–alkyne cycloaddition - Mazur, Maryna O.; Zhelavskyi, Oleksii S.; Zviagin, Eugene M.; Shishkina, Svitlana V.; Musatov, Vladimir I.; Kolosov, Maksim A.; Shvets, Elena H.; Andryushchenko, Anna Yu.; Chebanov, Valentyn A. (Beilstein Journal of Organic Chemistry, 2021)
A novel catalyst-free synthetic approach to 1,2,3-triazolobenzodiazepinones has been developed and optimized. The Ugi reaction of 2-azidobenzaldehyde, various amines, isocyanides, and acids followed by microwave-assisted intramolecular azide–alkyne cycloaddition (IAAC) gave a series of target heterocyclic compounds in moderate to excellent yields. Surprisingly, the normally required ruthenium-based catalysts were found to not affect the IAAC, only making isolation of the target compounds harder while the microwave-assisted catalyst-free conditions were effective for both terminal and non-terminal alkynes.
Keywords: click chemistry; microwave chemistry; multicomponent reactions; triazolobenzodiazepines; Ugi reaction

(untitled) - Banfi, L.; Basso, A.; Lambruschini, C.; Moni, L.; Riva, R. (Chem. Heterocycl. Compd., 2017)

(untitled) - Barlow, T. M. A.; Tourwé, D.; Ballet, S. (Eur. J. Org. Chem., 2017)

(untitled) - Vachhani, D. D.; Kumar, A.; Modha, S. G.; Sharma, S. K.; Parmar, V. S.; Van der Eycken, E. V. (Eur. J. Org. Chem., 2013)

(untitled) - Bertelli, L.; Biagi, G.; Giorgi, I.; Livi, O.; Manera, C.; Scartoni, V.; Martini, C.; Giannaccini, G.; Trincavelli, L.; Barili, P. L. (Farmaco, 1998)

(untitled) - Cameron, K. O.; Beretta, E. E.; Chen, Y.; Chu-Moyer, M.; Fernando, D.; Gao, H.; Kohrt, J.; Lavergne, S.; Jardine, P. D. S.; Guzman-Perez, A.; Hoth, C.; Perry, D. A.; et al. (Bioorg. Med. Chem. Lett., 2012)

(untitled) - Majumdar, K. C.; Ganai, S. (Synthesis, 2013)

(untitled) - Shafie, A.; Mohammadi-Khanaposhtani, M.; Asadi, M.; Rahimi, N.; Ranjbar, P. R.; Ghasemi, J. B.; Larijani, B.; Mahdavi, M.; Shafaroodi, H.; Dehpour, A. R. (Mol. Diversity, 2020)

(untitled) - Sudhapriya, N.; Nandakumar, A.; Arun, Y.; Perumal, P. T.; Balachandran, C.; Emi, N. (RSC Adv., 2015)

(untitled) - Arora, N.; Dhiman, P.; Kumar, S.; Singh, G.; Monga, V. (Bioorg. Chem., 2020)

(untitled) - Bariwal, J.; Kaur, R.; Voskressensky, L. G.; Van der Eycken, E. V. (Front. Chem. (Lausanne, Switz.), 2018)

(untitled) - Sharma, U. K.; Sharma, N.; Vachhani, D. D.; Van der Eycken, E. V. (Chem. Soc. Rev., 2015)

(untitled) - Vroemans, R.; Bamba, F.; Winters, J.; Thomas, J.; Jacobs, J.; Van Meervelt, L.; John, J.; Dehaen, W. (Beilstein J. Org. Chem., 2018)

(untitled) - Akritopoulou-Zanze, I.; Gracias, V.; Djuric, S. W. (Tetrahedron Lett., 2004)

(untitled) - Asgari, M. S.; Soheilizad, M.; Ranjbar, P. R.; Larijani, B.; Rahimi, R.; Mahdavi, M. (Tetrahedron Lett., 2019)

(untitled) - Barlow, T. M. A.; Jida, M.; Tourwé, D.; Ballet, S. (Org. Biomol. Chem., 2014)

(untitled) - Balalaie, S.; Vaezghaemi, A.; Zarezadeh, N.; Rominger, F.; Bijanzadeh, H. R. (Synlett, 2018)

(untitled) - Hu, J.; Cheng, Y.; Yang, Y.; Rao, Y. (Chem. Commun., 2011)

(untitled) - Pelkey, E. T.; Gribble, G. W. (Tetrahedron Lett., 1997)

(untitled) - Murlykina, M. V.; Kornet, M. N.; Desenko, S. M.; Shishkina, S. V.; Shishkin, O. V.; Brazhko, A. A.; Musatov, V. I.; Van der Eycken, E. V.; Chebanov, V. A. (Beilstein J. Org. Chem., 2017)

(untitled) - Arigela, R. K.; Mandadapu, A. K.; Sharma, S. K.; Kumar, B.; Kundu, B. (Org. Lett., 2012)

(untitled) - Johansson, J. R.; Beke-Somfai, T.; Said Stålsmeden, A.; Kann, N. (Chem. Rev., 2016)

(untitled) - De Moliner, F.; Bigatti, M.; De Rosa, C.; Banfi, L.; Riva, R.; Basso, A. (Mol. Diversity, 2014)

(untitled) - Xia, Y.; Chen, L.-y.; Lv, S.; Sun, Z.; Wang, B. (J. Org. Chem., 2014)